Numerical Simulation of Rarefied Gas Flows with Specified Heat Flux Boundary Conditions (Communications in Computational Physics, 2018)
We investigate unidirectional rarefied flows confined between two infiniteparallel plates with specified heat flux boundary conditions. Both Couette and force-drivenPoiseuille flows are considered. The flow behaviors are analyzed numericallyby solving the Shakhov model of the Boltzmann equation. We find that a zero-heat-fluxwall can significantly influence the flow behavior, including the velocity slip andtemperature jump at the wall, especially for high-speed flows. The predicted bimodal-liketemperature profile for force-driven flows cannot even be qualitatively capturedby the Navier-Stokes-Fourier equations.